PENGARUH INTRINSIC GOALS PADA COMPULSIVE BUYING (STUDI PADA MAHASISWI DI SEMARANG) - Euis Soliha; Pudji Utomo; Suzy Widyasari (Jurnal Ekonomi dan Bisnis Airlangga, 2012)
This research tries studies phenomenon behavior of negative purchasing in marketing world that is about compulsive buying. Compulsive buying defined as a chronic condition, where someone does repetitive purchasing that occurs as a negative events or feeling (Faber and O"Guinn, 1989). In this research, researcher examines how influence intrinsic goals at compulsive buying. Intrinsic goals are purpose of real person, like as self-acceptance, affiliation, and community feeling. Population in this research is students in Kota Semarang, with 104 respondents as sample. Researcher applies Multiple Linier Regression for answer the problem. Result of research indicates that Self-Acceptance Chance (SAC), Affiliation Chance (AFC), and Community Feeling Importance (CFI) influence compulsive buying.